2022
DOI: 10.3390/ma15207320
|View full text |Cite
|
Sign up to set email alerts
|

Short and Long-Term Solubility, Alkalizing Effect, and Thermal Persistence of Premixed Calcium Silicate-Based Sealers: AH Plus Bioceramic Sealer vs. Total Fill BC Sealer

Abstract: This study aimed to investigate the short- and long-term solubility, alkalizing potential, and suitability for warm-vertical compaction of AH Plus Bioceramic Sealer (AHBC), and Total Fill BC Sealer (TFBC) compared to the epoxy-resin sealer AH Plus (AHP). A solubility test was performed according to ISO specification 6876 and further similar to ISO requirements over a period of 1 month in distilled water (AD) and 4 months in phosphate-buffered saline (PBS). The pH of the immersion solution was determined weekly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 25 publications
(44 reference statements)
4
9
0
Order By: Relevance
“…It is important to highlight that the alkaline pH may play an important role in terms of antibacterial activity and healing processes [ 16 , 24 , 25 ]. Accordingly, similar pH values for AHP and AHPD were reported in previous studies [ 8 , 20 ]. In the present study, WRST demonstrated slightly higher pH values than those reported by Yamauchi et al [ 18 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It is important to highlight that the alkaline pH may play an important role in terms of antibacterial activity and healing processes [ 16 , 24 , 25 ]. Accordingly, similar pH values for AHP and AHPD were reported in previous studies [ 8 , 20 ]. In the present study, WRST demonstrated slightly higher pH values than those reported by Yamauchi et al [ 18 ].…”
Section: Discussionsupporting
confidence: 88%
“…AH Plus Bioceramic (Dentsply Sirona, Ballaigues, Switzerland) is a novel premixed bioceramic sealer, which has been introduced in the dental market. This sealer contains a reactive tricalcium silicate, but with a lower percentage of calcium silicate compared to existent bioceramic sealers due to the absence of di-calcium silicate within its composition [ 20 ]. Well-Root ST (Vericom, Chuncheon-si, Gangwon-Do, Korea) is a further modern premixed CS sealer, which contains calcium aluminosilicate as the reactive compound [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both calcium-silicate-based sealers presented alkaline pH values at all observation periods ( Figure 8 ), which agrees with a recent report [ 62 ]. At day 1 and after 14 days, Endosequence BC Sealer HiFlow showed significantly higher pH values than VDW.1Seal.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have demonstrated that heating these sealers reduces the setting time and flow [8,21,22] and increases solubility [23], making proper filling challenging. In contrast, other studies have shown that heating has minimal impact on the sealers' physicochemical properties [18,24,25]. Thus, whether and how heat application influences the physicochemical properties of various CSCSs warrants further investigation.…”
Section: Introductionmentioning
confidence: 94%